Evaluasi Manajemen Sumber Daya Teknologi Informasi pada Dinas Kependudukan dan Pencatatan Sipil (Dispendukcapil) Kota Batu Menggunakan Framework COBIT 5 dengan Fokus Domain EDM04, APO07 dan DSS03 - Mohammad Fachryza Purwanto Putra; Yusi Tyroni Mursityo; Alfi Nur Rusyidi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Dinas Kependudukan dan Pencatatan Sipil (Dispendukcapil) Kota Batu is a government body that utilizes the use of information technology (IT) in fulfilling the task of providing public services in the field of population registration and civil registration. To be able to maximize the quality of IT resources from Dispendukcapil Kota Batu, it is necessary to measure capability level and evaluate the process of ensuring IT resource optimization, human resource management processes, and problem management processes so that later it can be improved and improved in the quality management process IT. One method that can be used to measure and evaluate IT resource management processes is to use the COBIT 5 framework by focusing on the use of EDM04 (Ensure Resource Optimization) process, APO07 (Manage Human Resource) process and DSS03 (Manage Problems) process. Through the process of data retrieval, namely by conducting interviews, observations and measurement processes using assessment sheets, it is known that the capability level in the EDM04 process is at level 2, then the APO07 process is at level 2 and the DSS03 process is at level 1. Meanwhile, the expected targeted level of the entire EDM04, APO07, and DSS03 process is level 3. So that the known gap values ​​in the EDM04 and APO07 processes are worth 1 level and the gap value in the DSS03 process is worth 2 levels. In order for Dispendukcapil Kota Batu to reach the expected targeted level, recommendations need to be given that refer to base practices, work products, generic practices, and generic work products on COBIT 5.